The last kids on Earth / Max Brallier & Douglas Holgate - Brallier, Max (Viking, an imprint of Pengiun Random House LLC, 2015)
Ever since the monster apocalypse hit town, average thirteen year old Jack Sullivan has been living in his tree house, which he's armed to the teeth with catapults and a moat, not to mention video games and an endless supply of Oreos and Mountain Dew scavenged from abandoned stores. But Jack alone is no match for the hordes of Zombies and Winged Wretches and Vine Thingies, and especially not for the eerily intelligent monster known only as Blarg. So Jack builds a team: his dorky best friend, Quint; the reformed middle school bully, Dirk; Jack's loyal pet monster, Rover; and the fiercest girl Jack knows, June. With their help, Jack is going to slay Blarg, achieve the ultimate Feat of Apocalyptic Success, and be average no longer! Can he do it? Told in a mixture of text and black-and-white illustration, this is the perfect series for any kid who's ever dreamed of starring in their own comic book or video game.